Open-World Multimodal Understanding and Generation with Efficiently Finetuned Foundation Models - Chen, Long (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
With the astonishing ability of different pretrained foundation models (e.g., large language models (LLMs), vision-language models, diffusion models), today’s AI research and development tendency has been revolutionized. In this talk, I will answer two questions: Q1: How can we efficiently train or fine-tune foundation models? Q2: How can we build strong open-world multimodal understanding and generation models with these pretrained foundation models?